Cytokine function in medication-naive first episode psychosis: A systematic review and meta-analysis - Upthegrove, Rachel; Manzanares-Teson, Nuria; Barnes, Nicholas M. (Schizophrenia research, 2014)
This systematic review sets out to give a comprehensive overview of the cytokine profile at the onset of psychosis un-confounded by medication. We aim to provide insight into the early pathophysiological process of psychosis and areas for future research of potential biomarkers able to chart the extent of illness or effectiveness of treatment. Following PRISMA guidelines, a systematic primary search identified 4638 citations, 4651 studies were retrieved and screened, and 23 studies met the inclusion criteria (published in English before June 2013, patients with neuroleptic naive first episode psychosis, and assessed circulating cytokines). These reported 570 patients, 683 healthy control subjects, and 20 cytokine/cytokine receptors. Papers that contained sufficient stratified data were included in a random-effects pooled effect size meta-analysis. Highly significant effect sizes were found for elevated IL-1β, sIL-2r, IL-6, and TNF-α. Non-significant effect size estimates were obtained for IL-2, IL-4, and IFN-γ. Thus, we found significant elevation in pro-inflammatory cytokine levels in the serum of patients with medication-naive first episode psychosis. This adds to the evidence of a pro-inflammatory immune deregulation in schizophrenia and suggests these cytokines should be the focus for further research in biomarkers of progress and extent of illness. Future studies should focus on the medication-naive group at the early stages of illness with numbers large enough to allow for the control of other potential confounding factors.